Influence of externally damping on impact-induced soft tissue vibrations and muscle responses in landings - Fu, W.; Liu, Y.; Wang, X (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The aim of this study was to investigate the changes in activation of the musculoskeletal system in response to soft-tissue vibrations with different compression conditions (externally applied) in a drop-jump landing task. Twelve trained male participants were instructed to perform drop-jump landings from 3 heights in compression shorts (CS) and regular shorts without compression (CC). Externally induced soft-tissue vibration damping, i.e. reduced peak acceleration and increased damping coefficient, was associated with a significant decrease in muscular activity of the rectus femoris and the biceps femoris muscles during drop-jump landing from different heights. Therefore, a greater increase in the damping is associated with a greater decrease in muscle activity.